Public Sector Accountability to Implement Sustainable Development Goals in Sri Lanka: Influence of Traditional and Non-Traditional Donors - Keshara De Silva; Prem W Senerath Yapa; Gillian Vesty (Australasian Accounting, Business and Finance Journal, 2022)
Implementation of Sustainable development Goals (SDGs) for better environmental sustainability in developing countries in Asia has taken centre stage in response to the major environmental and social degradation created through rapid economic development in the region. Further, lack of clarity in environmental accountability of traditional economic developmental activities and internationally funded infrastructure development projects has resulted in reduced water and air quality and imperilled biodiversity. SDG related research in developing country context is limited and the impact of the funding bodies on public sector governance and accountability is scarce. This paper aims to fill this gap by addressing environmental accountability of public sector entities in internationally funded development projects in Sri Lanka, as a fast-developing country in Asia. The results indicate that environmental degradation is a continuing issue in Sri Lanka despite the efforts of traditional donor agencies monitoring and implementing environmental sustainability guidelines and SDG principles in infrastructure projects. The drastic change in the donor landscape experienced in the country with the rise of non-traditional donors and the deficiencies in public sector governance and accountability structures pose a significant threat to attainment of SDGs, including environmental sustainability in Sri Lanka.
Keywords: Accountability; Environmental Sustainability; SDGs; non-Traditional Donors; Public Sector; Infrastructure Funding; Sri Lanka